2020
DOI: 10.47743/saeb-2020-0006
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Audit and Environmental Disclosure Quality

Abstract: In this study we explore the association between environmental audit and the quality of environmental disclosure as measured by voluntary and timely disclosure. Relying on a multiple theory framework and using a sample of 81 French non-financial companies listed on the SBF 120 index covering the six-year period from 2012 to 2017, we found a positive and statistically significant relationship between the level of voluntary disclosure of environmental information and the environmental audit committee, the enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 70 publications
1
7
1
Order By: Relevance
“…e results showed that the timely disclosure of environmental information was affected by the environmental audit committee, CSR (Corporate Social Responsibility) committee, the auditors, earnings management behavior, firm size, and the industry, while no evidence has been found that there is a statistically significant relationship between CSR committee and the voluntary disclosure of environmental information [6]. Silva et al (2018) aimed to assess the potential and application of UAVs (Unmanned Aerial Vehicles) in environmental audit and proposed a method for data acquisition and identification of environmental impacts [7].…”
Section: Research Methods and Related Literature Onmentioning
confidence: 91%
See 1 more Smart Citation
“…e results showed that the timely disclosure of environmental information was affected by the environmental audit committee, CSR (Corporate Social Responsibility) committee, the auditors, earnings management behavior, firm size, and the industry, while no evidence has been found that there is a statistically significant relationship between CSR committee and the voluntary disclosure of environmental information [6]. Silva et al (2018) aimed to assess the potential and application of UAVs (Unmanned Aerial Vehicles) in environmental audit and proposed a method for data acquisition and identification of environmental impacts [7].…”
Section: Research Methods and Related Literature Onmentioning
confidence: 91%
“…e research emphasized the importance of green economy audit which may be a suitable auditing support mode for forestry enterprises [5]. Marwa et al (2020) discussed the relationship between environmental disclosure quality and environmental audit.…”
Section: Research Methods and Related Literature Onmentioning
confidence: 99%
“…Following the work of DeAngelo (1981), it has been widespread practice to distinguish between audit firms according to their brand name (i.e., big vs. small audit firms), and audit firms with a brand name tend to have better disclosure. Marwa et al (2020) find that there is a higher level of voluntary disclosure of environmental information when firms are audited by Big4 auditing firms. Similarly, Palmer (2008) shows that firms that are audited by higher‐quality auditors provide more disclosure in terms of both extent and quality.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Using the principles of systemicity and practicability, the efficiency index system of professional football clubs is constructed, and the importance of each index is analyzed [ 9 ]. At the same time, the environmental protection responsibility of sports clubs is helpful to the implementation of this research, and the corresponding theoretical basis is used to solve the problem of today's sports clubs performing environmental protection responsibilities [ 10 ]. Only by paying attention to and assuming the social responsibility related to economic benefits, and constantly raising new issues and discussing them, can sports clubs embody their greatest social value [ 11 ].…”
Section: Introductionmentioning
confidence: 99%